Nanocrystal delivery vehicle - Abu Bakar @ Zakaria, Md Zuki; Kamba, Abdullah Shafiu; Ismail, Maznah; Tengku Ibrahim, Tengku Azmi (2014)
The present invention relates to nanocrystal delivery vehicle, more particularly for delivery of drugs, peptides, protein, genes, anticancer, anti-inflammatory and other macromolecules. The nanocrystal is biobased aragonite calcium carbonate derived from cockle shells. In one application, the nanocrystal is able to release drug in response to changes in pH. The present invention also relates to the method of preparation of the nanocrystal delivery vehicle.